Advances in mesenchymal stem cell exosomes: a review - Tang, Yaya; Zhou, Yan; Li, Hong-Jun (Stem cell research & therapy, 2021)
Stem cells can be used for regenerative medicine and as treatments for disease. The application of tissue engineering-related transplantation, stem cells, and local changes in the microenvironment is expected to solve major medical problems. Currently, most studies focus on tissue repair and regeneration, and mesenchymal stem cells (MSCs) are among the most common research topics. MSCs are applicable as seed cells, and they represent one of the current hot topics in regenerative medicine research. However, due to storage limitations and because cell senescence occurs during in vitro expansion, their clinical application is challenging. Exosomes, which are secreted by MSCs through paracrine signalling, not only have the same effects as MSCs, but they also have the advantages of targeted delivery, low immunogenicity, and high repairability. This article reviews the acquisition methods, characteristics, biological functions, and clinical applications of exosomes.